Efficacy of Zest Application Timings in Irrigated Acetolactase Synthase-Resistant Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2019)
Acetolactase synthase inhibiting (ALS) herbicides were evaluated for efficacy in ALS-resistant grain sorghum. Kochia and quinoa control were similar among all herbicides tested regardless of evaluation date. Cinch ATZ alone preemergence, and Cinch plus Resolve and Harmony GT PRE followed by Zest POST controlled puncturevine 73-78%. Late-season green foxtail control was best when Zest was included as an early postemergence or postemergence application. Cinch ATZ applied alone preemergence, Cinch ATZ preemergence followed by Zest POST, and Cinch plus Resolve and Harmony GT PRE followed by Zest POST controlled Palmer amaranth 81–84%, and resulted in the highest grain yields.
Keywords: herbicide-tolerant sorghum